2020
DOI: 10.14744/anatoljcardiol.2020.27227
|View full text |Cite
|
Sign up to set email alerts
|

The risk of cardiovascular events in patients with metabolic syndrome: The results of a population based prospective cohort study (PURE Turkey)

Abstract: Objective: Metabolic syndrome (MetS) includes several cardiovascular (CV) risk factors. This study aimed to assess CV risk of MetS, contribution of its components to the risk, and whether MetS provides additional risk beyond its components. Methods: The Prospective Urban Rural Epidemiology (PURE) Turkey cohort included 3933 individuals aged between 35 and 70 years, with a median follow-up of 8.9 years. MetS was diagnosed as the presence of any of the following criteria:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…A large-scale meta-analysis conducted in Turkey reported a very high prevalence of MetS, especially in women, finding that 1 in every 4 men and 1 in every 3 women had MetS (10). The PURE study, where individuals of low and high socioeconomic status selected from the seven geographical regions of Turkey were followed up for 12 years, also reported that abdominal obesity, low HDL-C levels, high blood pressure, and dysglycemia were more common in women than in men (11).…”
Section: Discussionmentioning
confidence: 99%
“…A large-scale meta-analysis conducted in Turkey reported a very high prevalence of MetS, especially in women, finding that 1 in every 4 men and 1 in every 3 women had MetS (10). The PURE study, where individuals of low and high socioeconomic status selected from the seven geographical regions of Turkey were followed up for 12 years, also reported that abdominal obesity, low HDL-C levels, high blood pressure, and dysglycemia were more common in women than in men (11).…”
Section: Discussionmentioning
confidence: 99%
“…The present study also found a potential correlation between high TG and high fasting blood glucose levels ( p < 0.20); both of them caused myocardial structure and function impairments in pre-HF coronary heart disease patients ( p < 0.05). High TG and high fasting blood glucose levels are the main components of metabolic syndrome ( 27 ), indicating a close relationship between metabolic abnormalities and early cardiac dysfunction in coronary heart disease patients ( 28 , 29 ). Metabolic disturbances caused by high serum TG can contribute to subclinical myocardial injury and adverse cardiovascular outcomes ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the control group, the rs2479409 was associated with a lower risk of metabolic syndrome, a low risk of having increased alkaline phosphatase >p75, and a low risk of increased gamma-glutamyltranspeptidase. Several reports have shown that metabolic syndrome increases the risk of cardiovascular events [ 45 , 46 , 47 ]. Recent studies have suggested that an increased serum alkaline phosphatase is a predictor of cardiovascular disease and vascular calcification [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%